2013
DOI: 10.3168/jds.2012-6106
|View full text |Cite
|
Sign up to set email alerts
|

Veterinary herd health management programs on dairy farms in the Netherlands: Use, execution, and relations to farmer characteristics

Abstract: Veterinary herd health management (VHHM) programs are of growing importance to the dairy industry; they support farmers in the shift from curative to preventive health management, caused by increased herd sizes and quality standards in dairy farming. Farmers participating in VHHM are visited every 4 to 6 wk by their veterinarian, who checks the animals and herd management to intervene in a proactive way with problems regarding animal health and animal welfare. At present, no good overview exists of how VHHM is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
66
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 18 publications
(27 reference statements)
7
66
1
1
Order By: Relevance
“…Overall milk production and milk quality appeared to be better in farms of VHHM participants. This is in line with previous research (Derks et al, 2013). Longevity and fertility of the herd appeared to be worse.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Overall milk production and milk quality appeared to be better in farms of VHHM participants. This is in line with previous research (Derks et al, 2013). Longevity and fertility of the herd appeared to be worse.…”
Section: Discussionsupporting
confidence: 81%
“…It is, however, important to remember that the success of VHHM is, at least partly, dependent on the relationship and cooperation between farmer and veterinarian. Previous research has shown that the relationship farmers have with their veterinarian is a significant predictor for participation in VHHM (Derks et al, 2013). Also, veterinarians are not always aware of the goals the farmer wants to reach (Kristensen and Enevoldsen, 2008;Derks et al, 2012b;Hall and Wapenaar, 2012), although knowledge of the farmer's goals is important for compliance to veterinary advice (Sorge et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is in line with previous research showing that the veterinarian is being perceived as a highly trusted and influential referent in herd health management (e.g. Ellis-Iversen et al, 2010;Kristensen and Jakobsen, 2011;Lam et al, 2011;Derks et al, 2013;Fisher, 2013). This suggests that for future BT alike vaccination strategies, the social interactions between veterinarians and farmers might be an appropriate communication channel to use.…”
Section: Discussionsupporting
confidence: 80%